The Effect of a Chayotte (Sechium edule) Extracts (Decoct and Macerated) on the Labeling of Blood Elements with Technetium- 9m and on the Biodistribution of the Radiopharmaceutical Sodium Pertechnetate in Mice: an In vitro and In vivo Analysis - Dire, G.; Lima, E.; Gomes, M.; Bernardo-Filho, M. (Pakistan Journal of Nutrition, 2003)
The biodistribution of radiopharmaceutical used in diagnostic imaging can be altered by a wide variety of factors. If unknown, the drug interaction with radiopharmaceuticals can lead to misdiagnosis or the necessity to repeat the examination, increasing the dose to the patient. The constituents of herbal products can cause adverse effects. Although natural products are widely used as food or as medicines for humans they can alter the labeling of blood constituents with technetium-99m (99mTc) as wells as the bioavailability of the radiopharmaceutical sodium pertechnetate (99mTcO4Na). 99mTc is one of most used radio nuclide in nuclear medicine and in basic research. Some authors described that natural and synthetic drugs may alter the process of radio labeling. Sechium edule (chayotte) is a vegetable very spent in the human nutrition as the popular medicine due its properties such as the diuretic and the hypotensor effects. We evaluated the influence of a chayotte (Sechium edule) extracts (decoct and macerated) on the radio labeling of blood elements and on the bioavailability of 99mTcO4Na. In this study, blood was withdraw from Wistar rats and the aliquots of blood were incubated with the chayotte extracts decoct and macerated, 0.1g/mL) during 1 hour. After that, blood was incubated with stannous chloride (SnCl2) for 1 hour together with the adding of 99mTc in each breaks of 15min until 1 of incubation with SnCl2 . In each 10 min an aliquot of blood was taken and then plasma (P) and blood cells (BC) were isolated, also precipitated with trichloroacetic acid (TCA 5%) and soluble (SF) and insoluble fractions (IF) were separated. For the biodistribution analysis, the 99mTcO4Na (0.3mL) was administrated into male Wistar rats which had drunk or not the extract (macerated) for 60 days. After 10 min, the animals were sacrificed, the organs were isolated, the radioactivity determined in a well counter and the percentages of radioactivity per gram (%ATI/g) in the organs was calculated. For the radio images analysis, the animals were treated with the extracts (macerated and decoct) during 15 days, after this period of time, it was administrated doses of 100μCi of 99mTcO4Na in the ocular plexus of the animals. The images were obtained after 10min. The qualitative analysis of the images was done. The analysis of the results has demonstrated that the extracts have increased the labeling of blood elements with 99mTc which was incubated together with SnCl2, in the times 0 and 30 min to decoct extract (time 0 min: labeling in the C: from 37.97 ± 0.31 to 59.70 ± 0.56; and in the FIC: from 61.76 ± 0.75 to 73.15 ± 0.37; time 30min: labeling in the C: from 84.06 ± 0.91 to 94.75 ± 0.87; and in the FIC: from 76.72 ± 0.26 to 85.37 ± 0.67) and in the times 15 and 30 min to macerated extract (time 15min: labeling in the C: from 29.04 ± 0.31 to 50.13 ± 0.82; time 30min: labeling in the C: from 75.39 ± 0.77 to 83.42 ± 0.51). The %ATI/g was altered in the thyroid (from 4.57 ± 0.58 to 2.03 ± 1.33); lung (from 0.84 ± 0.25 to 0.21 ± 0.02); stomach (from 5.19 ± 1.34 to 2.03 ± 0.60) and blood (from 50.07 ± 3.36 to 32.25 ± 2.32). In the qualitative analysis it was observed an decreased in the performance of the images related to the stomach region. Due to the biodistribution it was related that an extract of eggplant was capable of altering the bioavailability of 99mTcO4Na different of a cauliflower extract which has not been able to alter it. It is possible to suggest that some components of chayotte extracts present an oxidant power able to alter the biodistribution of 99mTcO4Na, as a tip, we speculate that the referred extract metabolized in the liver may induce the generation of reactive metabolites with oxidant properties, this fact could justify the alteration of the uptake in the organs.